Regional Benches of the Supreme Court of India - The Path Ahead - Mishra, Sankalp (Christ University Law Journal, 2021)
There is a need for the establishment of regional benches of the Supreme Court. By the analysis of various statistical data, the paper puts forward the urgent need for widening the reach of the Supreme Court and also to rejuvenate and reestablish the tarnishing reputation of the Supreme Court as an ordinary court of appeal. The paper explores the essential reasons for the establishment of benches of Supreme Court that can be broadly divided into three heads namely (i) wide access to justice (ii) Supreme Court reduced to an ordinary court of appeal (iii) litigation as a measure of well-being. The paper also analyses the recommendations laid out in the 95th, 120th, 125th and 229th Law Commission reports and analyses problem in hand, on the basis of analysis and the immediate need for the reform of the judicial system.